Twenty Years of G-CSF Clinical and Nonclinical Discoveries - Molineux, Graham; Foote, MaryAnn; Arvedson, Tara (Milestones in Drug Therapy,, 2012)
Granulocyte colony-stimulating factor (G-CSF or GCSF) is a secreted glycoprotein that stimulates the proliferation and differentiation of granulocyte precursor cells, and induces mobilization of peripheral blood progenitor cells from the bone marrow. Development of recombinant human G-CSF has had a profound impact on the treatment of many diseases, including severe chronic neutropenia and cancer, and has enabled peripheral stem cell transplantation to supplant bone marrow transplantation in the autologous setting. This Milestones in Drug Therapy volume describes the experience of the last 20 years of treatment with recombinant human G-CSF, including the basic science, the use of recombinant human G-CSF in both the oncology and nononcology settings, and the safety and economics of its use. Many of the authors were the original investigators of recombinant human G-CSF and other authors are key researchers who provide their outlook for the next 20 years for use of and research with recombinant human G-CSF.